Enhanced Immunoreceptor Tyrosine-based Activation Motif Signaling is Related to Pathological Bone Resorption During Critical Illness - Vanhees, I.; Gunst, J.; Janssens, T.; Wauters, A.; Van Herck, E.; Van Cromphaut, S.; Van den Berghe, G.; Owen, H. C. (Hormone and Metabolic Research, 2013)
Prolonged critically ill patients present with distinct alterations in calcium and bone metabolism. Circulating bone formation markers are reduced and bone resorption markers are substantially elevated, indicating an uncoupling between osteoclast and osteoblast activity, possibly resulting in pronounced bone loss, impaired traumatic or surgical fracture healing, and osteoporosis. In addition, we have previously shown that increased circulating osteoclast precursors in critically ill patients result in increased osteoclastogenesis in vitro, possibly through FcγRIII signaling. In the current study, we investigated the effects of sustained critical illness on bone metabolism at the tissue level in a standardized rabbit model of prolonged (7 days), burn injury-induced critical illness. This in vivo model showed a reduction in serum ionized calcium and osteocalcin levels, as is seen in humans. Trabecular area, bone mineral content, and density were decreased in sick rabbits [by 43% (p<0.01), 31% (p<0.01), and 29% (p<0.05), respectively], as was the trabecular gene expression of osteoblast and angiogenesis markers, indicating decreased bone formation and impaired vascularization. There was no change in the expression of osteoclast differentiation markers from the canonical RANK/RANKL/OPG pathway, however, there was an increase in expression of markers from the non-canonical, immunoreceptor tyrosine-based activation motif (ITAM) signaling pathway, FcγRIII, and DAP12 (148% and 59%, respectively; p<0.01). The current study has shown a detrimental effect of prolonged critical illness on trabecular bone integrity, possibly explained by reduced osteoblast differentiation and angiogenesis, coupled with increased osteoclastogenesis signaling that may be mediated via the non-canonical immunoreceptor tyrosine-based activation motif signaling pathway.
Keywords: intensive care unit; bone hyperresorption; osteoclast; osteoblast; ITAM